Marching with enthusiasm, politicizing with fear: the case of Belgrade 2001 pride parade in the context of early stage democratic transition - Vranić, Bojan; Ilić, Nikola (Frontiers in Political Science, 2025)
In June 2001, Serbian LGBTQIA+ civil society organizations endeavored to organize the first Pride parade in Belgrade, marking the second such event in post-communist countries in the aftermath of 1989. Despite drawing around 100 participants to Belgrade’s central square, the parade culminated in violence, with 40 LGBTQIA+ activists sustaining injuries from a group of 1,000–2000 hooligans and football fans. Existing literature often portrays the 2001 Pride event as a violent episode, focusing on a narrative of victimization that has shaped LGBTQIA+ activism in Serbia for the past two decades. However, this narrative tends to overlook or insufficiently address the political dynamics that fueled the violence. This study seeks to explore the repercussions of the limited socio-political engagement of LGBTQIA+ groups, highlighting their challenges in mobilizing broad-based, multi-sectoral support by failing to connect LGBTQIA+ rights with broader societal issues such as gender equality and minority rights. Through interviews with the 2001 parade activists, LGBTQIA+ rights experts, and political representatives this research aims to bridge the knowledge gap concerning the complex political landscape and ongoing democratic blockages faced by these groups. The authors contend that the LGBTQIA+ community’s pursuit of autonomy and professionalization, amidst a transformed post-revolution political climate, left them vulnerable to violent backlash from ultra-nationalistic factions.